1997
DOI: 10.1128/jb.179.21.6729-6735.1997
|View full text |Cite
|
Sign up to set email alerts
|

A tricarboxylic acid cycle intermediate regulating transcription of a chloroaromatic biodegradative pathway: fumarate-mediated repression of the clcABD operon

Abstract: The ortho-cleavage pathways of catechol and 3-chlorocatechol are central catabolic pathways of Pseudomonas putida that convert aromatic and chloroaromatic compounds to tricarboxylic acid (TCA) cycle intermediates. They are encoded by the evolutionarily related catBCA and clcABD operons, respectively. Expression of the cat and clc operons requires the LysR-type transcriptional activators CatR and ClcR, respectively, and the inducer molecules cis,cis-muconate and 2-chloro-cis,cis-muconate, respectively. The regu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
50
0
2

Year Published

1998
1998
2017
2017

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 67 publications
(52 citation statements)
references
References 38 publications
0
50
0
2
Order By: Relevance
“…Growth on TCA cycle intermediates has been reported to cause carbon catabolite repression and to repress the expression of many operons at the transcriptional level in Pseudomonas (7,24,34). McFall et al (22) suggested that the growth and metabolism of some bacteria and yeasts were repressed during growth with TCA cycle intermediates and that this repression was found at the transcriptional level.…”
Section: Discussionmentioning
confidence: 99%
“…Growth on TCA cycle intermediates has been reported to cause carbon catabolite repression and to repress the expression of many operons at the transcriptional level in Pseudomonas (7,24,34). McFall et al (22) suggested that the growth and metabolism of some bacteria and yeasts were repressed during growth with TCA cycle intermediates and that this repression was found at the transcriptional level.…”
Section: Discussionmentioning
confidence: 99%
“…The mechanism of catabolic repression of the 2,4,6-TCP degradation pathway in JMP134 by glutamate is unknown, but can occur at the transcriptional level, as reported in Pseudomonas spp. (19,31).…”
Section: Discussionmentioning
confidence: 99%
“…There is also experimental evidence for competition of several compounds on the regulatory protein. For example, fumarate reversibly inhibits the formation of the clcA transcript in in vitro transcription assays in the presence of purified ClcR and 2-chloro-cis,cis-muconate (138). The presence of cis,cis-muconate decreases the affinity of the BenM protein for benzoate (31).…”
Section: Lysr Family Of Transcriptional Regulators Catabolic Operons mentioning
confidence: 99%